1994
DOI: 10.1111/j.1439-0507.1994.tb00421.x
|View full text |Cite
|
Sign up to set email alerts
|

White piedra and Trichosporon species in equatorial Africa. I. History and clinical aspects: an analysis of 449 superficial inguinal specimens

Abstract: Summary. White piedra is a hair infection characterized by nodules composed of fungal elements which envelop the hair shaft. Classically, this infection was considered to be produced by an asexual yeast‐like fungus, Trichosporon beigelii. At present, in accordance with studies carried out previously, this species is subdivided into six newly defined distinct species (T. asshu, T. ovoides, T. inkin, T. mucoides, T. asteroides and T. cutaneum), all belonging to the class Basidiomycetes. Although widespread, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Three species were recognized: T. mucoides (25 strains), T. inkin (20 strains), and T. asahii (seven strains). 6,7 The identity of these strains was confirmed by means of an agglutination method performed with monospecific antisera. This method allowed the verification of the presence of antigens common to the genera Cryptococcus and Trichosporon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three species were recognized: T. mucoides (25 strains), T. inkin (20 strains), and T. asahii (seven strains). 6,7 The identity of these strains was confirmed by means of an agglutination method performed with monospecific antisera. This method allowed the verification of the presence of antigens common to the genera Cryptococcus and Trichosporon.…”
Section: Discussionmentioning
confidence: 98%
“…In the 1990s, it was observed that T. mucoides was sometimes responsible for white piedra. 5,6 Previously, white piedra was considered to be caused by Trichosporon beigelii. Subsequently, this species was divided into six distinct species: Trichosporon asahii, Trichosporon asteroides, Trichosporon cutaneum, Trichosporon inkin, T. mucoides, and Trichosporon ovoides.…”
Section: Discussionmentioning
confidence: 99%
“…is known worldwide as white piedra and is considered a sporadic infection that occurs in tropical and temperate climates (Fishman et al 1980, Thérizol-Ferly et al 1994, Elmer et al 2002, Youker et al 2003, Ghorpade 2004, Kiken et al 2006, mostly in rainy periods (Kamalam et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…White piedra, a mycosis that occurs in some animals, such as horses, monkeys and domestic animals, as well as humans (Kaplan 1959), is found within a wide geographical distribution, including tropical and temperate regions, occurring mainly in South America, Africa, Europe and Asia (Kamalam et al 1981, Thérizol-Ferly et al 1994, Ghorpade 2004, Schwartz 2004). There are also some cases in the USA (Elmer et al 2002, Youker et al 2003, Kiken et al 2006 and it has been found to be endemic to Texas (Kalter et al 1986).…”
mentioning
confidence: 99%
“…In dermatological and fungal study recently carried out in Libreville (Gabon) we were able to distinguish 52 Trichosporon strains isolated from female patients from this humid tropical region [7,8]. Since we have long been interested in the identification of yeast species by slide agglutination tests [9] we tried, in the present study, to assess the applicability of these methods in the identification of Trichosporon species according to the new classification of GuCho et al [4,5].…”
mentioning
confidence: 99%